2019
DOI: 10.3390/s19030522
|View full text |Cite
|
Sign up to set email alerts
|

Investigating EEG Patterns for Dual-Stimuli Induced Human Fear Emotional State

Abstract: Most electroencephalography (EEG) based emotion recognition systems make use of videos and images as stimuli. Few used sounds, and even fewer studies were found involving self-induced emotions. Furthermore, most of the studies rely on single stimuli to evoke emotions. The question of “whether different stimuli for same emotion elicitation generate any subject-independent correlations” remains unanswered. This paper introduces a dual modality based emotion elicitation paradigm to investigate if emotions can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 57 publications
2
17
0
1
Order By: Relevance
“…The motor cortex is mainly located in the central anterior gyrus of the cerebral cortex, where electrodes of AF3 and AF4 are located in the forehead, electrodes of F3 and F4 are located in the frontal area, and electrodes of F7 and F8 are located in the lateral forehead. Related studies [40] showed that some electrode channels appear more frequently in the subjects, the frontal brain area is more important under artificial induction.…”
Section: Discussion and Conclusion A Discussionmentioning
confidence: 96%
“…The motor cortex is mainly located in the central anterior gyrus of the cerebral cortex, where electrodes of AF3 and AF4 are located in the forehead, electrodes of F3 and F4 are located in the frontal area, and electrodes of F7 and F8 are located in the lateral forehead. Related studies [40] showed that some electrode channels appear more frequently in the subjects, the frontal brain area is more important under artificial induction.…”
Section: Discussion and Conclusion A Discussionmentioning
confidence: 96%
“…Their results are better than those of; Koelstra et al [6]—62% and 56%; Atkinson and Campos [43]—73% and 73%; Yoon and Chung [44]—70% and 70%; Naser and Saha [45]—66% and 64% for arousal and valence. Masood and Farooq [46] used Common Spatial Patterns (CSP) from 14 EEG channels and LDA to analyze fear emotions using two different stimuli and obtained classification accuracies between 55% and 73%.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, physiological emotion recognition also plays an important role in emotion recognition, which can be inferred from different ways such as biometric [132], [133], EEG signal measurements [134], [135]. As discussed above, these approaches also have the same approaches, such as data collection, pre-processing, and computational intelligence methods, to infer emotions.…”
Section: D: Physiological Emotion Recognitionmentioning
confidence: 99%